The Reproductive Biology of Scad Fish (Decapterus sp.) at Pelabuhan Perikanan Nusantara Pengambengan Jembrana, Bali - Vidyastari, Odjastira; Watiniasih, Ni Luh; Pebriani, Dewa Ayu Angga (Advances in Tropical Biodiversity and Environmental Sciences; Vol 4 No 1 (2020): ATBES, 2020)
Scad fish is one of the economically important fish species, which landed in Pengambengan fishing port. This study aimed to investigate the biological aspects of scad fish such as its growth, measured length and weight, and reproduction aspects such as sex ratio, gonad maturity level (GML), gonad maturity index (GMI), and fecundity. Method in this research is observation. Samples of scad fish were collected every two weeks using the simple random sampling. The total number of samples was 200 fishes, collected from November to December 2019. The result showed that length 18.3-23.06 cm and weight 53.31-112.58 g. The sex ratio of male and female was 1.2:1 consisting of 122 males and 88 females. Scad fish found had 97 fishes GML III, 96 fishes GML IV, and 7 fishes having GML V. GMI value scad fish is 0,014%-0,074%, that fish spawn more than once every year and fecundity was 7687-40588.